2010
DOI: 10.1029/2010gl044544
|View full text |Cite
|
Sign up to set email alerts
|

Electron density and temperature measurements in the cold plasma environment of Titan: Implications for atmospheric escape

Abstract: [1] We present electron temperature and density measurements of Titan's cold ionospheric plasma from the Langmuir probe instrument on Cassini from 52 flybys. An expression of the density as a function of temperature is presented for altitudes below two Titan radii. The density falls off exponentially with increased temperature as log(n e ) = −2.0log(T e ) + 0.6 on average around Titan. We show that this relation varies with location around Titan as well as with the solar illumination direction. Significant hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 23 publications
4
44
0
Order By: Relevance
“… Ågren et al [2009] studied the ionospheric density and temperature profiles using the voltage sweep data from the Langmuir probe on board the Cassini spacecraft. Edberg et al [2010] used the same data now extended to 52 flybys and showed that there is a logarithmic dependence between the ionospheric densities and temperatures. Latest in a series of upper atmosphere composition studies using the Cassini Ion and Neutral Mass Spectrometer results is a study by Magee et al [2009].…”
Section: Introductionmentioning
confidence: 99%
“… Ågren et al [2009] studied the ionospheric density and temperature profiles using the voltage sweep data from the Langmuir probe on board the Cassini spacecraft. Edberg et al [2010] used the same data now extended to 52 flybys and showed that there is a logarithmic dependence between the ionospheric densities and temperatures. Latest in a series of upper atmosphere composition studies using the Cassini Ion and Neutral Mass Spectrometer results is a study by Magee et al [2009].…”
Section: Introductionmentioning
confidence: 99%
“…Remote measurements by radio occultation as well as in situ measurements have revealed that the ionospheric structure can vary significantly with time and that the electron density levels can be sporadically much higher than normal at Titan, i.e., during single flybys, likely due to increased levels of precipitating particles causing impact ionization [ Kliore et al , , ; Edberg et al , ]. Statistical studies using in situ Langmuir probe measurements have shown that although there is considerable variations in the shape of the ionospheric altitude profiles, the density and peak altitude of the ionosphere have stayed rather constant around the values stated above [ Ågren et al , ; Edberg et al ].…”
Section: Introductionmentioning
confidence: 99%
“…In the ionosphere, at altitudes between 900 and 1600 km, where chemistry is dominated by ion-molecule reactions, the ion (Crary et al 2009) and neutral (De la Haye et al 2007) temperatures are not exactly equal and vary in the ranges 100-200 K and 145-160 K, respectively. Thus, one can conclude that the characteristic average temperature for ion-molecule reactions is about 150 K. In Titan's atmosphere, the electron temperature ranges from 150 to 10,000 K (Edberg et al 2010), lying between 150 K and 1000 K range in the ionosphere (Richard et al 2011), where ion-electron recombination plays a major role.…”
Section: Chemistry In Titan's Atmospherementioning
confidence: 99%